Cantilever Micro-rheometer for the Characterization of Sugar Solutions - Robert W. Stark; Stefan Burghardt; Marc Hennemeyer (Sensors, 2008)
The volume required for the rheological characterization of fluids can beminimized by using micromechanical cantilevers as viscosity sensors. Here, a simplemeasurement tool for the characterization of sugar solutions is proposed. The sensorconsists of a micromechanical cantilever as used in an atomic force microscopy which isintegrated into a closed fluid handling system. Fluid properties are derived from an analysisof the power spectral density of the fluctuations of the cantilever deflection signal. The dataacquisition system is operated with standard consumer computer components, which limitsthe costs for the hardware. Measurements with different sugar solutions indicate that thesensor system provides reliable viscosity values for sugar concentrations as they occur inbiological systems. The viscosities of the sugar solutions could be evaluated with an errorsmaller than 5 %.